Preparation of a Topical Product from Allium sativum Retrieved from Iranian Traditional Medicine - Maryam Jahandideh; Paria Kharazi; Zahra Jafariazar; Shirin Fahimi* (Iranian Society of Pharmacognosy, 2019)
Background and objectives: Garlic (Allium sativum L.) oil has been introduced in Iranian traditional medicine (ITM) as an effective topical agent for urine dribbling. Additionally, the beneficial effects of garlic on prostatic proliferation have been revealed in recent studies. The purpose of this research was formulation of a topical ointment using garlic oil proposed by ITM and quality control of the product. Methods: Garlic oil was prepared according to ITM instructions and analysed using GC/MS method. In order to formulate garlic ointment, several experimental formulations were examined. Microbial tests as well as physical assessments including thermal stability evaluation and study of rheological behaviour were performed on the final product. Results: GC/MS analysis of garlic oil showed the presence of dialyl trisulfide, one of the major organo-sulfur components of garlic. The herbal ointment containing garlic oil (70%), white petrolatum (23.7%) and white beeswax (6%), showed suitable physical properties as well as plastic tixotropic behaviour and was free of any microbial contamination. Conclusion: Regarding the modern evidences about the beneficial effects of garlic and its sulphur compounds on improvement of BPH and prevention of prostate cancer, garlic ointment could be an appropriate candidate for studies in the field of prostate related diseases with respect to its traditional use in ITM.